2014
DOI: 10.2478/aut-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pet Fibres Surface Enzymatic Modification on the Selected Properties

Abstract: The effect of changes in the surface structure of glossy polyester filaments from poly(ethylene terephthalate) in terms of its micro-topography, molecular and supermolecular structure of the fibre surface layers on selected fibre surface and volumetric properties has been assessed. The performed tests and measurements have shown that the change in the general surface characteristics of PET fibres (micro-topography and hydrophilicity) results in very beneficial changes in both their volumetric (dyeability) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Many studies based on tensile test have confirmed that the surface modification of PET fabrics using EDA reduces their mechanical properties. [46] In this study, the sample treated with EDA for 4 hours could not be tested so a sample treated for 3 hours was chosen for the statistic. A treatment with EDA causes greater damage to the fabric compared to the other amino-based reagents.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies based on tensile test have confirmed that the surface modification of PET fabrics using EDA reduces their mechanical properties. [46] In this study, the sample treated with EDA for 4 hours could not be tested so a sample treated for 3 hours was chosen for the statistic. A treatment with EDA causes greater damage to the fabric compared to the other amino-based reagents.…”
Section: Resultsmentioning
confidence: 99%